Nurses’ attitudes towards euthanasia - Orzeł, Zbigniew; Kwietniewska, Sylwia; Sutryk, Mariusz; Niwińska , Kamila; Kutnik, Blanka; Guz, Ewa (Journal of Education, Health and Sport, 2021)
Aim Euthanasia is a difficult moral and controversial topic in society as well as among medical professionals. It is a topic avoided by society, but we hear about it more and more. In Poland, there is no universal consent for euthanasia, it is forbidden, although in some countries patients have the right to it. The main aim of the study was to find out about the opinions and attitudes of actively working nurses on euthanasia. Objective The aim of this study was to find out about the opinions and attitudes of the respondents, i.e. nursing staff, about euthanasia in the pilot studies. Material and methods 106 nurses employed in health facilities in the Krasnystaw and Chełm poviats were qualified for the study. The method of diagnostic survey was used in the work. The main research tool was a self-constructed, proprietary questionnaire. The survey questionnaire was evaluated. First, the assessment was made by three competent judges (doctors and a nurse), then a pilot study was carried out on 10 people. The questionnaire did not require any corrections. The pilot studies were not included in the main studies. All results were analyzed using Microsoft Office Excel 2010. Results 106 people took part in the study: 34 women and 72 men. The average age of the respondents was 40 years. Statistical analysis showed that most of the respondents are opposed to euthanasia and its legalization in Poland. Significant differences occurred on the level of dependencies between socio-demographic factors determining the attitude towards euthanasia. Conclusions The results of the conducted research show certain tendencies and dependencies that should be checked by expanding the research in a larger group of people working as nurses and nurses.